Health Professionals Perceived Concerns and Challenges in Providing Palliative and End-of-Life Care: A Qualitative Analysis. (April 2019) - Price, Deborah M.; Strodtman, Linda K.; Montagnini, Marcos; Smith, Heather M.; Ghosh, Bidisha
Background: The Institute of Medicine identifies that quality palliative/end-of-life (EOL) care should be provided to patients with serious, life-limiting illnesses and their families by competently prepared health professionals. Purpose: This study assessed perceived concerns of health professionals pertaining to the delivery of palliative/EOL care in the hospital setting. The specific aim was to determine thematic concerns in the delivery of palliative/EOL care which emerged from respondents' impressions of a memorable palliative/EOL patient experience. Methods: Interdisciplinary health professionals at a large academic health system in the Midwest were surveyed to reflect upon a memorable palliative/EOL life care patient situation (positive or negative). A Thematic Analysis approach was used to code qualitative responses to 4 open-ended questions and then extract themes and subthemes from the coded data. Results: Concerns identified by participants (N = 425) emerged around 7 themes including communication (97%), decision-making/care planning (75%), education needs (60%), EOL care (48%), ethics (24%), satisfaction with care (9%), and spiritual/cultural sensitivity (6%). Conclusion: Challenges exist in the delivery of quality palliative/EOL care in the hospital setting which may be addressed through educational initiatives that focus on recognition of cultural influences on care preferences, improving communication between patients/families and providers, education about the differences between palliative and EOL care, and increased competency of health providers in having EOL/goals-of-care discussions. Health professionals must recognize the benefit of collaborative palliative care in order to meet patient and family needs holistically and comprehensively.